MUSLIM PROGRESIF (Telaah Pemikiran Omid Safi tentang Keadilan, Gender dan Pluralisme) - Listiana, Heni (Universitas Islam Madura, 2015)
It’s about time to Islam people to make a change to go to aspiration executing command of Allah Swt. Its Moment also forwarded to Islam people esteem human as Allah award which must be taken care of, to be looked after and defended. Idea carried by progressive Moslem, one of the trend idea of Islam, to realize social justice, justice of gender, and pluralism become idea which must inspire humanly of us as part of mankind in all the world coming from Prophet Adam. Without differentiating background, tribe, religion, race and gender, progressive Moslems have to fight against all existing injustice around us. Do not only criticize to be conducted by injustice which is from Islam people but also dare to criticize injustice from West. It is Important here to have Multiple-critics which was begun by progressive Moslem. Bargaining social justice, justice of and gender of pluralism have fresh wind to bring to understanding of Islam people in looking at abysmal social reality of difference of boundaries. Going to secure and prosperous and fair society.